AN FTIR STUDY OF TETRAHEDRALLY COORDINATED FERROUS IRON IN THE SPINEL-HERCYNITE SOLID SOLUTION - Skogby H.; Hålenius U. (My University, 2003)
Room-temperature FTIR spectra of ten chemically and structurally well-characterized synthetic spinel-hercynite solid solution single crystals containing between 4 and 98 mol% hercynite component show that absorption in the range 2500–7000 cm−1 is linearly correlated (R2 = 0.995) with IVFe2+ concentration. The integral molar absorption coefficient for this absorption equals 1.49·108 cm/mol. In addition, the structure of the absorption envelope in this spectral region remains unchanged throughout the entire composition range. These two findings are consistent with assignments to a spin-allowed electronic d-d transition (5E → 5T2) in IVFe2+, split by the dynamic Jahn-Teller effect, and demonstrate that next-nearest interactions in Fe clusters have little or no effect on this absorption feature at ambient conditions.